The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.17576/3l-2019-2504-11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PWIM in the ESL Classroom: Vocabulary Knowledge Development Among Primary Malaysian Learners

Abstract: The present quasi-experimental study examined the impact of pictures, via a modified version of Emily Calhoun's (1999) Picture Word Inductive Model (PWIM), on the English vocabulary acquisition of Malaysian Year 1 pupils in a rural national primary school. Meara and Buxton's (1987) Yes-No Recognition Test (YNRT) was adapted and further tested for reliability to measure the recall and retention of subjects' vocabulary size. A total of 60 subjects participated in the research, comprising two intact classes; one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In accordance with literature review (Calhoun, 1999;Gu & Lornklang, 2021;Jiang, 2018;Lee et al, 2019;Srithamma & Songserm, 2020;Triwahyuni et al, 2020), PWIM directs student reading events, as follows:…”
Section: Theoretical Background Teaching Readingmentioning
confidence: 72%
See 1 more Smart Citation
“…In accordance with literature review (Calhoun, 1999;Gu & Lornklang, 2021;Jiang, 2018;Lee et al, 2019;Srithamma & Songserm, 2020;Triwahyuni et al, 2020), PWIM directs student reading events, as follows:…”
Section: Theoretical Background Teaching Readingmentioning
confidence: 72%
“…The PWIM instructional method utilizes images as a trigger for language experience tasks (Joyce & Weil, 2004). PWIM has been utilized successfully in both L1 (Triwahyuni et al, 2020) and L2 (Gu & Lornklang, 2021;Jiang, 2018;Lee et al, 2019) instruction, particularly with lower age groups (Calhoun, 1999). In AR-reading platforms (Wahyuni et al, 2020), the PWIM teaching approach is preferred for vocabulary instruction.…”
Section: Discussionmentioning
confidence: 99%
“…Asyiah (2017) and Wangdi (2020) stated that word knowledge is one of the prerequisite language skills that is closely associated with the success of language acquisition. Supporting this, decades of studies have strongly acknowledged the need for adequate words for the betterment of one's language abilities and to meet comprehensible and standard communication skills (Lee et al, 2019;Matthews & Cheng, 2015;Peters & Webb, 2018). In light of this, this study investigated the EFL university students' attitudes towards Coxhead's AWL, after they had self-learned it, in enhancing their academic receptive and productive skills.…”
Section: Discussionmentioning
confidence: 99%
“…Vocabulary knowledge was mostly measured because it is believed to be one of the most essential components of language, particularly in second language acquisition (Lee et al, 2019;Choo et al, 2017). Indeed, it is commonly stated as the heart of language acquisition (Coady and Huckin, 1997) as it defines the learners' mastery in the target language.…”
Section: Why Vocabulary and Grammar?mentioning
confidence: 99%
“…Indeed, it is commonly stated as the heart of language acquisition (Coady and Huckin, 1997) as it defines the learners' mastery in the target language. Good lexical knowledge of any language enables learners to master the target language and help improve their communicative skills ( Lee et al, 2019). Alqahtani (2015) reported that learners can acquire the target language only through acquiring their corresponding vocabulary, and the researcher also suggested that both teachers and learners must know the essence of vocabulary for the successful acquisition of the target language.…”
Section: Why Vocabulary and Grammar?mentioning
confidence: 99%